Meta-Analysis the Effect of Gadget Use on Language Development in Children - Liza Laela Abida; Nur Fitri Ayu Pertiwi; Mohammad Ali (Jurnal Fisioterapi dan Kesehatan Indonesia, 2022)
Gadgets that are used excessively and not controlled can have a negative impact on psychology and children cannot smoothly socialize or communicate with their surroundings. Preschoolers experience a process of rapid physical, motor, intellectual, emotional, language and social development. Gadgets are equipped with features such as social media, video, audio, images and games so that children are addicted and become lazy to move or do activities. This situation can affect a child's development. a number of related articles that the use of gadgets can increase the delay in language development in children. The purpose of this study was to estimate the magnitude of the effect of using gadgets on language development in children by conducting a meta-analysis on the same number of articles.